DRUG QUERY SYSTEM WITH SIDE EFFECTS PREDICTION USING SEMI-SUPERVISED APPROACH - Hemasri M , Dhivagar S , Hariharan L ,Kavin R, Mathanagopalan N (International Journal of Advanced Science and Technology, 2020)
Drug prescription calls for attention of numerous factors, such as drug interactions and side results. The method is further complicated by way of the reality that the presence of a few drug homes, which includes aspect effects, relies upon on affected person traits, consisting of age and gender. Our purpose is to provide a tool to help scientific practitioners in prescribing pills. We growth an method to impeach for drugs that satisfy ahard and fast of conditions based totally on drug houses. Numerous precautions want to be taken within the usage of pharmaceutical tablets, for each healthcare experts, who prescribe and administer drugs, and for clients of medicine